2022
DOI: 10.1101/2022.03.25.22272948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Labor market participation and depression during the COVID-19 epidemic among young adults (18 to 30 years): a nationally representative study in France

Abstract: Objective: To examine the relationship between young adults labor force participation and depression in the context of the COVID-19 pandemic. Design, Setting, Participants: Data come from the nationally-representative EPICOV cohort study set up in France, and were collected in 2020 and 2021 (3 waves of online or telephone interviews) among 2217 participants aged 18-30 years. Participants with prior mental health disorder (n=50) were excluded from the statistical analyses. Results: Using Generalized Estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…These experiences of emotional stress due to the COVID-19-induced economic crisis represent critical risk factors for mental health challenges ( Achdut & Refaeli, 2020 ; de Miquel et al, 2022 ; Graupensperger et al, 2022 ; Ranta et al, 2020 ; Shanahan et al, 2022 ), including depression, the prevalence of which has steadily increased among young adults in recent decades ( Mojtabai et al, 2016 ). Previous studies have also showed that young adults with lower family income ( Basheti et al, 2021 ; Browning et al, 2021 ; Yang & Yang, 2022 ), and those who experienced income loss, job insecurity or unemployment due to the pandemic were more likely to report depressive symptoms ( Ganson et al, 2021 ; Melchior et al, 2022 ; Thorndike et al, 2022 ). These findings underscore the need to further investigate the role of financial support strategies on mental health outcomes among young adults.…”
Section: Introductionmentioning
confidence: 95%
“…These experiences of emotional stress due to the COVID-19-induced economic crisis represent critical risk factors for mental health challenges ( Achdut & Refaeli, 2020 ; de Miquel et al, 2022 ; Graupensperger et al, 2022 ; Ranta et al, 2020 ; Shanahan et al, 2022 ), including depression, the prevalence of which has steadily increased among young adults in recent decades ( Mojtabai et al, 2016 ). Previous studies have also showed that young adults with lower family income ( Basheti et al, 2021 ; Browning et al, 2021 ; Yang & Yang, 2022 ), and those who experienced income loss, job insecurity or unemployment due to the pandemic were more likely to report depressive symptoms ( Ganson et al, 2021 ; Melchior et al, 2022 ; Thorndike et al, 2022 ). These findings underscore the need to further investigate the role of financial support strategies on mental health outcomes among young adults.…”
Section: Introductionmentioning
confidence: 95%